2019
DOI: 10.38061/idunas.657975
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Oleic Acid Coated Magnetic Nanoparticles for Hyperthermia Applications

Abstract: The present study focuses on obtaining highly stable iron oxide nanoparticles (IONs), stabilized by the coating of oleic acid (OA) for magnetic nano hyperthermia (MNH) applications. For this purpose, bare and different amounts of oleic acid (0.2%, 0.5% and 1.0%, v/v) coated IONs were prepared by co-precipitation method. Then, their structures, morphologies, magnetic properties and heating abilities were characterized by using suitable techniques. IONs+1.0%OA nanoparticles showed low agglomeration with high dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For instance, Giri et al [83], synthetized magnetite NP with similar sizes of 10-12 nm and obtained a lower ILP value (0.22 nHm 2 kg −1 ). Likewise, Senturk and co-workers produced magnetite NP with 8.3 ± 1.6 nm and an ILP of 0.23 was obtained [84]. This value is also higher than the value obtained by Shete et al [85] even for a higher magnetite NP size (21.8 ± 5 nm, 0.42 nHm 2 kg −1 ).…”
Section: Hyperthermia Measurementsmentioning
confidence: 70%
See 2 more Smart Citations
“…For instance, Giri et al [83], synthetized magnetite NP with similar sizes of 10-12 nm and obtained a lower ILP value (0.22 nHm 2 kg −1 ). Likewise, Senturk and co-workers produced magnetite NP with 8.3 ± 1.6 nm and an ILP of 0.23 was obtained [84]. This value is also higher than the value obtained by Shete et al [85] even for a higher magnetite NP size (21.8 ± 5 nm, 0.42 nHm 2 kg −1 ).…”
Section: Hyperthermia Measurementsmentioning
confidence: 70%
“…Concerning the post-synthesis coating with fucoidan (sample MF, mean size of 11.7 nm ± 3.1), the highest SLP value was obtained (156 W g −1 ) corresponding to an ILP value of 2.6 nHm 2 kg −1 . This thermal efficiency is superior in comparison with other reported coated magnetite particles (Table 4), including polyethylene glycol (PEG), [61,87] chitosan, [85] polycaprolactone (PCL), [88] dextran, [16] dimercaptosuccinic acid (DMSA) [89], silica, [90] poly-L-lysine, [91] oleic acid, [84] and folic acid [92]. Ghosh et al [87], through a co-precipitation method, obtained magnetite NP post-synthesis coated with polyethylene glycol (PEG) with a medium size of 10 nm and an ILP value of 0.1 nHm 2 kg −1 , which is much lower than the value resulted from MF.…”
Section: Hyperthermia Measurementsmentioning
confidence: 86%
See 1 more Smart Citation
“…The previous studies showed that the concentrations of OA influenced the hydrodynamic size of SPIONs. [ 5 ] The addition of OA will form a protective monolayer that is linked to the surface of SPIONs and will form highly uniform and monodisperse SPIONs. [ 15 ] The larger hydrodynamic size could be the reason for increasing the polydispersity index.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method produces highly agglomerated SPIONs resulting in less effectiveness in biomedical application. [ 5 6 ] Therefore, controlling the particle size and particle distributions of SPIONs is very crucial to avoid the SPION agglomerations and becomes a determinant of the synthesis process. SPIONs with particle sizes more than 100 nm can lose their magnetic properties easily because of oxidation and high chemical activity.…”
Section: Introductionmentioning
confidence: 99%